Effects of the application of the amniotic membrane in the healing process of skin wounds in rats - Campelo,Mariana Barbosa Dias (2018)
Abstract Purpose: To evaluate the efficacy of the application of the human amniotic membrane (HAM) on the inflammatory process, fibroblast proliferation, formation of collagenand reduction of skin wound areas in rats. Methods: Thirty six rats were submitted to a surgical injury induction and divided into two groups (n = 18): group C (control) and T (treated with the HAM). The macroscopic evolution in the wound area and the histological characteristics of the skin samples were evaluated. Results: The regression of the wound area was greater in group T. The histological analysis revealed a significant reduction (p < 0.05) in the inflammatory infiltrate in group T at all experimental periods compared with that in the control group. Furthermore, the group T presented a significant increase in the proliferation of fibroblasts at 14 and 21 days compared with group C (p < 0.05). Regarding the deposition of mature collagen fibers, there was an increase in the replacement of type III collagen by type I collagen in group T (p < 0.05). Conclusion: Treatment with the HAM reduced the healing time as well as the inflammatory responses, increased the proliferation of fibroblasts, and induced a higher concentration of mature collagen fibers.